2014
DOI: 10.1111/1756-185x.12410
|View full text |Cite
|
Sign up to set email alerts
|

In vivoquantification of mouse autoimmune arthritis by PET/CT

Abstract: Aim To quantify the progression and severity of mouse collagen-induced arthritis (CIA) using an in vivo imaging tool, 18F-fluorodeoxyglucose (18F-FDG) PET/CT, and validate it against gold standard ‘histopathological’ evaluation. Method The PET radiotracer 18F-FDG, a marker for glucose metabolism, was injected in mice at different stages during the development of CIA and the radiotracer distribution was imaged using a PET scanner. A sequential CT scan provided correlated anatomy. Radiotracer concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…This result was in concordance with our earlier study [5], albeit that study was performed in a small number of animals. PS was determined to have a median value of 1Á02 (range 5 0Á85-1Á05) on day 0.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This result was in concordance with our earlier study [5], albeit that study was performed in a small number of animals. PS was determined to have a median value of 1Á02 (range 5 0Á85-1Á05) on day 0.…”
Section: Resultssupporting
confidence: 93%
“…Arthritis was induced (n 5 30) using type II bovine collagen (CII) [5,8,10] in eight-week-old arthritissusceptible male/1J mice (Jackson Laboratory, ME, USA). Arthritis was induced (n 5 30) using type II bovine collagen (CII) [5,8,10] in eight-week-old arthritissusceptible male/1J mice (Jackson Laboratory, ME, USA).…”
Section: Induction Of Ciamentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that 18 F-FDG was suggested as a good tool to develop the therapeutic effect of novel therapies of inflammatory arthritis in the study by Kundu-Raychaudhuri et al (42), in a preclinical model Laverman et al showed that 18 F-FDG was inferior to other nuclear imaging tracers when correlating uptake of 18 F-FDG with arthritis score (8).…”
Section: Discussionmentioning
confidence: 99%